[SOLVED]-4.3.1 find quadratic eq given 3 pts

karush

Well-known member
how do you find the quadratic equation given (-3,0) (3,0) and (0,-4)

thus y=k(x-3)(x+3) for the zero's but how do you find k or any other better method of finding the equation

thanks much

Last edited:

Jameson

Staff member
This can be done by looking at the general form of a quadratic equation: $$\displaystyle y=ax^2+bx+c$$. We need to solve for a,b and c in order to write our equation and we have three points so we can do this through substitution. First use (0,-4) for (x,y) and you get $$\displaystyle -4=a(0)^2+b(0)+c$$ which means that c=-4. Now use the other two points the same way and you will have to solve a two variable system of equations for a and b. Once you have a,b and c you have your answer.

Opalg

MHB Oldtimer
Staff member
how do you find the quadratic equation given (-3,0) (3,0) and (0,-4)

thus y=k(x-3)(x+3) for the zero's but how do you find k or any other better method of finding the equation
Starting from y=k(x-3)(x+3) (which gives the value 0 when x = 3 or –3), all you need to do is to put x=0 to see that y = –9k when x=0. But you want y to be –4 when x=0. Therefore –9k = –4. So k = 4/9, and $y = \frac49(x-3)(x+3).$

Fernando Revilla

Well-known member
MHB Math Helper
how do you find the quadratic equation given (-3,0) (3,0) and (0,-4)
Another way (if you have covered the Lagrange Interpolation Polynomial):

$y=0L_1+0L_2-4L_3=-4\dfrac{(x+3)(x-3)}{(0+3)(0-3)}=\dfrac{4}{9}(x+3)(x-3)$

karush

Well-known member
Another way (if you have covered the Lagrange Interpolation Polynomial):

$y=0L_1+0L_2-4L_3=-4\dfrac{(x+3)(x-3)}{(0+3)(0-3)}=\dfrac{4}{9}(x+3)(x-3)$
no have not heard of it. looks valuable tho so will look it up thanks

karush

Well-known member
$y = \dfrac{4}{9}(x-3)(x+3)$

ok I can't seem to write tikx to plot this

$\begin{tikzpicture}[scale=0.50] %preamble \usepackage{pgfplots} \begin{axis}[xmin=-3.5, xmax=3.5, ymin=-5, ymax=5, axis lines=middle, ticks=none] \addplot[ draw = black, smooth, ultra thick, domain=-4:4, ] {exp((4/9)*(x^2-9)} foreach \x in {-3,3} { (axis cs:{\x},0) node[below left] {\x} }; \end{axis} \end{tikzpicture}$
$$y = \dfrac{4}{9}(x-3)(x+3)$$